Sacubitril–valsartan versus enalapril for the treatment of acute decompensated heart failure in Chinese settings: A cost-effectiveness analysis - Hu, Tianyang; Liu, Yiting; Lou, Yake (Frontiers in Pharmacology, 2023)
Background: The episode of acute decompensated heart failure (ADHF) is the main cause of heart failure (HF) hospitalization. Sacubitril-valsartan has been proved to be effective in reducing the risks of HF hospitalization in ADHF. When to initiate the sacubitril-valsartan in ADHF is most cost-effective in China remains unclear. Methods: A life-time Markov model with 1 month cycle length was developed to evaluate the cost-effectiveness of early or late initiation of sacubitril-valsartan versus enalapril in ADHF. Early initiation of sacubitril-valsartan meant that sacubitril-valsartan was initiated after the stabilization from ADHF, and late initiation of sacubitril-valsartan meant that sacubitril-valsartan was initiated after stabilization from HF, defined not hospitalized for at least 3 consecutive months. The primary outcome was incremental cost-effectiveness ratio (ICER), expressed as the ratio of incremental cost to incremental effectiveness. Secondary outcomes were total costs, total effectiveness. Three times of per capita GDP of China in 2021 was set the willingness-to-pay threshold. One-way sensitivity analysis and probabilistic sensitivity analysis was employed to test the robustness of the results. Results: The early initiation of sacubitril-valsartan treatment resulted in an ICER of 3662.4 USD per quality adjusted life year, lower than the willingness-to-pay threshold, and the late initiation of sacubitril-valsartan treatment gained an ICER of 4444.4 USD/QALY, still lower than the willingness-to-pay threshold. One-way sensitivity analysis showed that our results were robust, and probabilistic sensitivity analysis suggested that early initiation of sacubitril-valsartan in ADHF was cost-effective under 97.4% circumstance. Conclusion: Early initiation of sacubitril-valsartan after stabilization of ADHF is of high cost-effectiveness compared with enalapril, late initiation of sacubitril-valsartan after stabilization of HF is still cost-effective, but not so cost-effective as early initiation of sacubitril-valsartan in ADHF. For Chinese ADHF patients, the time to initiate sacubitril-valsartan should be when patient is stabilized from ADHF, rather than stabilized from HF, from the perspective of economic evaluation.